(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Al6061 was particulate with various reinforcement composite metal matrix materials adding different matrices using stir casting method. Reinforcement of hybrid composites used to various kinds of applications such as good wear resistance, electrical semiconductor and development of mechanical properties. The characteristics of various combinations of Aluminium reinforcement material were investigated. Wear behavior has investigated by using pin-on- disc mechanism. Using Scanning Electron Microscope (SEM) examined in this investigation. Using optical microscopic to identifying the various worn surfaces such as Ploughing, debris and oxide layer. Pin-on-wear mechanism were carried out the reinforcement of Aluminium with different prepared composites of wear parameters such as sliding distance 300mm, sliding speed 2.5m/s and applying load 5N, 10N, 15N. This analysis result focused on minimum wear, coefficient of friction, frictional load and temperature effect. Experimental result shows the amount of adding composite particles to increasing the wear resistance and decreasing wear losses. From the effect of wear as curve fitting technique was applied for the polynomial and power law equation. These equations of R2 value higher than power law equations and much agreed with the experimental observation.